Ophthalmologic Phenotype–Genotype Correlations in Patients With Oculocutaneous Albinism Followed in a Reference Center - Seguy, Paul-Henri; Korobelnik, Jean-François; Delyfer, Marie-Noëlle; Michaud, Vincent; Arveiler, Benoit; Lasseaux, Eulalie; Gattoussi, Sarra; Rougier, Marie-Bénédicte; Trin, Kilian; Morice-Picard, Fanny; Ghomashchi, Nathalie; Coste, Valentine (Investigative ophthalmology & visual science, 2023)
Albinism is a group of genetic disorders that includes several conditions related to a defect in melanin production. There is a broad phenotypic and genotypic variability between the different forms. The aim of this study was to assess the ophthalmologic characteristics according to patients' genotypes in a cohort followed in the Reference Center for oculocutaneous albinism (OCA) of Bordeaux University Hospital, France.PurposeAlbinism is a group of genetic disorders that includes several conditions related to a defect in melanin production. There is a broad phenotypic and genotypic variability between the different forms. The aim of this study was to assess the ophthalmologic characteristics according to patients' genotypes in a cohort followed in the Reference Center for oculocutaneous albinism (OCA) of Bordeaux University Hospital, France.A retrospective observational study was conducted in a cohort of patients with OCA seen in consultation in the ophthalmology department between 2017 and 2021 in whom a genetic analysis was performed.MethodsA retrospective observational study was conducted in a cohort of patients with OCA seen in consultation in the ophthalmology department between 2017 and 2021 in whom a genetic analysis was performed.In total, 127 patients with OCA were included in this study and matched with the results of the genetic analysis. In the population aged over 6 years, there was no statistical difference in binocular visual acuity between the OCA1, OCA2, and OCA4 forms (P = 0.27). There was difference in ametropia between the three forms (P = 0.003). A two-by-two comparison using the Bonferroni correction showed a significant difference in ametropia between the OCA2 and OCA4 forms (P = 0.007) and between the OCA1 and OCA2 forms (P = 0.0075). Regardless of the form, most patients (75.4%) had grade 4 foveal hypoplasia. There was no association between the grade of foveal hypoplasia and the gene involved (P = 0.87).ResultsIn total, 127 patients with OCA were included in this study and matched with the results of the genetic analysis. In the population aged over 6 years, there was no statistical difference in binocular visual acuity between the OCA1, OCA2, and OCA4 forms (P = 0.27). There was difference in ametropia between the three forms (P = 0.003). A two-by-two comparison using the Bonferroni correction showed a significant difference in ametropia between the OCA2 and OCA4 forms (P = 0.007) and between the OCA1 and OCA2 forms (P = 0.0075). Regardless of the form, most patients (75.4%) had grade 4 foveal hypoplasia. There was no association between the grade of foveal hypoplasia and the gene involved (P = 0.87).We described a genotype-phenotype correlation for the three most represented forms of albinism in our cohort. This study allowed assessing the degree of visual deficiency in young children with OCA.ConclusionsWe described a genotype-phenotype correlation for the three most represented forms of albinism in our cohort. This study allowed assessing the degree of visual deficiency in young children with OCA.